Assessing how the South African National Standard 15489 improve the importance and usability of the archive: case of the Universities of Venda and WItwatersrand. (17th June 2021) - Netshakhuma, Nkholedzeni Sidney
Abstract : Purpose: This paper aims to assess how the South African National Standard (SANS) 15489 improves the importance and usability of the archives at the University of Venda (UNIVEN) and the University of Witwatersrand (WITS). Design/methodology/approach: Both quantitative and qualitative methods are used to assess how the standards improve the importance and usability of the archives. A total of 34 participants were selected to participate in the study; the choice of the population was because they are responsible for records management decisions in various divisions, departments and units. Data was obtained through structured interviews and observation. The study has established that there was much dissonance concerning records and archives management standards. Ethics approval was obtained from both the WITS and the UNIVEN research department. Informed consent was obtained from university staff members. Findings: The research found that only the WITS adopted SANS 15489. This was shown by the availability of a classification system (file plan) and retention schedule while the UNIVEN did not value SANS 15489 standards to manage all records created. Research limitations/implications: Although South Africa has 26 public universities, this study is only confined to the UNIVEN and the WITS. The researcher only focusses on the classification of records and disposal of records elements of SANS 15489. Practical implications: The findings have practical implications in that they can be used for assessing the archives and records management programmes. Other related universities can also use the findings as a reference point in the planning of university archives and records management programmes. Social implications: The findings were to assist the university authorities as decision and policymakers to ensure that records and archives management practices adhere to SANS 15489. Originality/value: Few studies related to the assessment of records management programme in universities in South Africa is not yet fully conducted in South Africa public universities. This study could be a valuable input for universities to adopt SANS 15489 standards to develop and implement records management programmes.